Check-in check-out : managing hotel operations - Vallen Gary K. (Harlow, 2009)
Check-In, Check-Out provides complete coverageof the hotel's front office and all of the support positions that make it work. Organized to reflect how a guest moves through the hotel (reservations, arrival, billing, departure, etc.) this edition provides a broad view of lodging management and covers unique topics such as corporate housing, destination elevators, and trade advertising contracts. Key industry changes are addressed throughout such as hotel technology, the greening of the industry, security issues and automation. Over 200 exhibits illustrate chapter content and help to create a work that both students and professional hoteliers seek out
Keywords: Hotel management; Motel management